The Proteins of Type IV Secretion System as Promising Candidates for Helicobacter Pylori Vaccine (Global Journal of Medical Research, 2015)
Helicobacter. pylori is a component of class 1 carcinogens and there is a close association between the incidence of gastric cancer and high prevalence of infection with this bacterium. The risk of gastric cancer associated with H. pylori infection in industrialized and developing countries is estimated to be 80% and 70% respectively. CagA is the important virulence factor in this bacterium and all of the strains involved in gastric cancer are CagA positive. This factor is secreted into host cells by type IV secretion system. CagA and type IV secretion system in H. pylori encoded by the cag pathogenicity islands (cag PAI) that encodes 30 proteins which are necessary for the pilus formation and function of type IV secretion system, so regarding to the role of this secretion system in secreting CagA and its function in pathogenesis and cancer development in humans and the role of different proteins of this secretion system such as canal and pilus formation and their necessity for function of these structures, it is possibly they are be appropriate candidates for design vaccine, because with inhibiting these proteins can stop canal and pilus formation and finally hinder CagA secretion into the host cells.